+0  
 
0
131
1
avatar+155 

help

 Oct 28, 2019
 #1
avatar+109202 
+1

4x^2  + 3y^2 -16x + 9y + 16  = 0       rearrange as

 

4x^2 - 16x  + 3y^2 + 9y =  -16          complete the square on x and y

 

4(x^2 - 4x  + 4)  +  3(y^2 + 3y + 9/4)  =  -16 + 16  + 27/4

 

4 (x - 2)^2  + 3(y + 3/2)^2  =  27/4         multiply through by  4/27

 

(16/27)(x - 2)^2  + (12/27)(y + 3/2)^2  =  1

 

16(x - 2)^2          12 (y + 3/2)^2

_______   +         _________  =     1

  27                            27

 

16 ( x - 2)^2           4(y + 3/2)^2

__________  +     __________    =    1

      27                          9

 

 

cool cool cool

 Oct 28, 2019

21 Online Users

avatar
avatar